Kiwifruit maturation, ripening and environmental response is not affected by CENTRORADIALIS (CEN) gene-editing. Issue 4 (2nd October 2021) - Wang, Ruiling; Nardozza, Simona; Nieuwenhuizen, Niels J.; Wang, Tianchi; Wang, Mindy Y.; Boldingh, Helen L.; David, Karine M.; Atkinson, Ross G.; Burdon, Jeremy N.; Allan, Andrew C.; Varkonyi-Gasic, Erika; Schaffer, Robert J.
ABSTRACT: Previous studies have shown the conversion of the perennial kiwifruit ( Actinidia spp.) to continuously flowering allows rapid cycling of generations. These plants are smaller, flower earlier and do not undergo dormancy. They provide a model system to rapidly test gene function in flowers and fruit, and allows for continuous production of fruit rather than seasonal production. In this study, the fruit of continuously flowering, CENTRORADIALIS ( CEN ) gene-edited, yellow-fleshed 'Hort16A' kiwifruit lines were assessed for a range of fruit quality characters. The fruit were smaller and often misshapen, but maturation and ripening occurred on a similar timeline to those of orchard-grown fruit. A single edited CEN line with balanced vegetative-floral production and fruit maturation was selected to assess the effects of growing conditions on fruit maturation and ripening. By lowering the temperature of the plants during maturation, starch breakdown and fruit softening were induced and degreening slowed. This result shows that despite the gene-edited plants flowering continuously and not experiencing a period of winter dormancy, the fruit they produce can complete a full cycle of development and ripening, and these fruit may be manipulated in a predictable manner through temperature within the controlled growing environment.